Sensory analysis and acceptability of pet food - Di Donfrancesco, Brizio (Kansas State University, 2016)
The pet food industry represents a competitive and growing part of the food industry that is constantly looking for innovation to differentiate products in the market. In recent years, the pet food market has undergone a humanization trend that has transformed pet owners into parents. In the light of this trend, pet owner acceptance has become even more crucial to product developers as the owners are the ones who make purchasing decisions. Performing descriptive sensory analysis on pet foods utilizing a human panel can assist in understanding the sensory characteristic of products. Knowing the sensory profile of pet food can then be useful in product development, in order to relate the descriptive data with palatability data from pets and to understand specific sensory attributes that drive pet liking. At the same time descriptive analysis can help understand what drives consumer acceptance of the products. The first objective of the research was to develop a sensory lexicon that could assist researchers and sensory professionals working in the pet food industry to describe appearance, aroma, flavor, and texture characteristics of dry dog food. More than seventy sensory terms were identified, defined, and referenced. The second objective was to utilize this sensory lexicon to understand relationships between sensory properties of products and pet owners’ liking. Results indicated that appearance played a major role in driving consumer liking of dry pet food. The next objective of the research was to understand sensory qualities and acceptance of extruded dry dog food manufactured with different fractions of red sorghum through some of the developed concepts. Sorghum is an important crop to Kansas that represents the first producer in USA. Sorghum characteristics such as a low glycemic index and antioxidant properties make it a perfect fit for pet food industry. A process such as extrusion may then help improve some negative characteristics such a lower digestibility that has been associated with sorghum in the past. Descriptive sensory analysis was performed and results indicated that aroma and flavor profile of the sorghum diets were not dissimilar to the ones of a control diet manufactured with rice, wheat, and corn, grains that are typically used by the pet food industry. Acceptance of pet owners was then assessed through a Central Location Test involving 105 consumers. The whole sorghum diet resulted to be the most liked sample by consumers, at the same level of the control diet. The next objective was then to understand how the experimental diets would be accepted by pets compared in a home situation. Thirty dogs were fed the diets in their own household environment over 20 consecutive days. No differences in acceptance for the diets were found. The last portion of the research was to determine volatile compounds present in the four diets and try to identify possible relationship with the sensory properties of the samples. Thirty-six compounds were identified with aldehydes being the most abundant volatiles group. Several relationships with sensory characteristics of samples were found.
Keywords: Sensory; Consumer; Pet food; Lexicon; Descriptive analysis; Sorghum